Nanotechnology in Drug Delivery for Liver Fibrosis - Gu, Lihong; Zhang, Feng; Wu, Jinhui; Zhuge, Yuzheng (Frontiers in Molecular Biosciences, 2022)
Liver fibrosis is a reversible disease course caused by various liver injury etiologies, and it can lead to severe complications, such as liver cirrhosis, liver failure, and even liver cancer. Traditional pharmacotherapy has several limitations, such as inadequate therapeutic effect and side effects. Nanotechnology in drug delivery for liver fibrosis has exhibited great potential. Nanomedicine improves the internalization and penetration, which facilitates targeted drug delivery, combination therapy and theranostics. Here, we focus on new targets and new mechanisms in liver fibrosis, as well as recent designs and development work of nanotechnology in delivery systems for liver fibrosis treatment.